Development of batik motifs in swim wear clothing with digital printing techniques - Wesnina, Wesnina; Albar, Yoga Matin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The research will be carried out for one year located in Jakarta. The purpose of this study is to obtain data and assessment of bomber jacket products with the application of contemporary Indonesian motifs. This research is a follow-up research on the Exploration of Ornamental Varieties of the Archipelago in the Form of Contemporary Motifs with Digital Techniques for Textile Design. From the results of previous research motifs, contemporary motifs with a variety of archipelago ornaments were produced. In this study, the motif will be applied to swimsuits. The motif applied was chosen by adjusting the shape and function of the women's swimsuit. A swimsuit is a sportswear that is used in a sports atmosphere, precisely in water. So far, women's swimsuits are more plain or patterned with lines and identities from a company. So in this study, the researcher tried to make a swimsuit with contemporary motifs typical of the archipelago. This study is an explanatory study that uses the survey method. The methodology used is the mix method. The analysis method used is descriptive analysis. This study adapts the purposive sampling technique. Purposive sampling is a sampling technique based on the data obtained in this study, first in the form of interview results from five expert panelists in the field of sports education and fashion practitioners which are analyzed descriptively. Then the second is the results of the questionnaire and acceptability in women aged 17-25 years. The research was conducted from February to September 2023. From this method, an assessment of swimsuits that are in accordance with the research objectives and adolescent acceptability will be found. Through this research, it is hoped that it can contribute to the design of contemporary motifs typical of the archipelago that are applied to fashion products, one of which is swimsuits. This can also add value to the love for the local culture of the archipelago which is implemented through contemporary motifs. In addition, it is hoped that it can be a reference and reference in the application of typical Indonesian motifs in the world of education and business.